Struktur Makro pada Kasus Ferdy Sambo di Media Online - Zeny Arisa Alfiyah Rofi; Elen Inderasari (Ikaprobsi, 2023)
This article aims to describe the macro structure that focuses on topics regarding the Ferdy Sambo case in the online media Kompas.com, Republika.co.id, and JawaPos.com. This research also aims to see the form of choice of words or sentences used by the online media Kompas.com, Republika.co.id, and JawaPos.com in news titles. The theory used in van Dijk’s discourse analysis regarding macro structure. This research method is qualitative, descriptive in nature. The results of this research have a macro structural form, namely the revelation of the premeditated murder that killed Brigadier J, the re-enactment of the murder scene of Brigadier J, the dismissal of Ferdy Sambo, the impact of the case of Brigadier J’s death, the hearing of Ferdy Sambo’s indictment, the trial of Ferdy Sambo’s prosecution, the defense hearing by Ferdy Sambo, and the verdict hearing of defendant Ferdy Sambo. The word from in the news title Republika.co.id contains five euphemistic expressions and Kompas.com contains two euphemistic expressions. However, on JawaPos.com there are no euphemistic expressions in the news title. Artikel ini bertujuan untuk mendeskripsikan struktur makro yang berfokus pada topik mengenai kasus Ferdy Sambo di media online Kompas.com, Republika.co.id, dan JawaPos.com. penelitian ini juga bertujuan untuk melihat bentuk pilihan kata atau kalimat yang digunakan media online Kompas.com, Republika.co.id, dan JawaPos.com dalam judul berita. Adapun teori yang digunakan analisis wacana van Dijk mengenai struktur makro. Metode penelitian ini ialah kualitatif yang bersifat deskriptif. Hasil penelitian ini terdapat wujud struktur makro yakni terungkap rekayasa pembunuhan berencana yang menewaskan Brigadir J, reka ulang adegan pembunuhan Brigadir J, pemberhentian Ferdy Sambo, dampak kasus kematian Brigadir J, sidang pembacaan dakwaan Ferdy Sambo, Sidang tuntutan Ferdy Sambo, Sidang Pembelaan oleh Ferdy Sambo, dan Sidang vonis terdakwa Ferdy Sambo. Bentuk kata dalam judul berita Republika.co.id terdapat lima ungkapan eufemisme dan Kompas.com terdapat dua ungkapan eufemisme. Namun, pada JawaPos.com tidak terdapat ungkapan eufemisme dalam judul berita.